A Review of Hydrogels, with its Properties and Applications in Medicine - Kumar Soni, Rakesh; M Kewatkar, Shailesh; Jain, Vidhi; Singh Saluja, Manmeet (Journal of Biomedical and Pharmaceutical Research, 2023)
A hydrogel is an insoluble in water three-dimensional polymer network that has the potential to absorb bodily fluids in a biological setting. Hydrogels may also be used in medical applications. Chemical crosslinking mechanisms such as optical polymerization, enzymatic reactions, and physical crosslinking mechanisms such as temperature- and pH-dependent processes, as well as ionic crosslinking, are all responsible for the formation of a network of polymers of this kind. Both physical and chemical hydrogels may be generated by the application of weak secondary forces, but chemical hydrogels can also be formed through the application of covalent forces. Hydrogels may be made from a wide variety of polymers derived from either natural or synthetic sources. The swelling, the mechanical characteristics, and the biological properties of hydrogels are some of the most essential aspects of hydrogels, and each of these qualities may have an effect on the structure and morphology of the hydrogel. Hydrogen is utilized in a variety of medical applications, including tissue engineering, contact lenses, wound dressings, and the release of therapeutic agents. This is possible because hydrogen has a structure that is analogous to the extracellular matrix (ECM), and it also has the ability to absorb water. There is a discussion on hydrogels, the many varieties of hydrogels, the characteristics of hydrogels, and their uses in medicine.